Pakistan at 100 : Growth and Investment - Waheed, Muhammad (World Bank, Washington, DC, 2019)
This policy note was prepared in parallel to the report Pakistan at 100, Shaping the Future. The report Pakistan at 100 discusses options to accelerate and sustain growth in Pakistan so that the country becomes an upper middle-income country when it turns 100 years old in 2047. This policy note discusses Pakistan achieving an advantageous environment for public and private investment by strengthening its business climate and reforming the financial sector.